2011
DOI: 10.1007/s11426-010-4169-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, DNA binding and cleavage studies of the copper(II) complexes of PNA-cyclen conjugates

Abstract: Two dinucleotide PNA-cyclen copper(II) complexes with -PNA (P1) and classical PNA (P2) backbones were synthesized and characterized. The interactions between title complexes and DNA were investigated under physiological conditions. Fluorescence studies indicate that the binding ability of complex P1 to CT-DNA is as twice as that of P2. DNA melting experiments were also carried out and the results show that T m caused by P1 is higher than that caused by P2. Agarose gel electrophoresis experiments demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Indeed, other studies have reported on similar copper complexes (bearing DNA intercalators) that cleave DNA via an oxidative pathway in the absence of adjuvants. 41,42 However, since the inhibitory effects of NaN 3 and KI could also be mediated by their ability to displace the copper-coordinated water, these data do not rule out the possibility that a hydrolytic mechanism contributes to the nuclease activity. Indeed, UV−vis spectroscopic analysis of the mixture of Cu(II)-cyclen with NaN 3 , KI, or NaCl (Supplementary Figures S4−6) reveal that NaN 3 and KI displace the Cu(II) associated water while the NaCl does not (i.e., at the ratio used in the scavenging assay).…”
mentioning
confidence: 93%
“…Indeed, other studies have reported on similar copper complexes (bearing DNA intercalators) that cleave DNA via an oxidative pathway in the absence of adjuvants. 41,42 However, since the inhibitory effects of NaN 3 and KI could also be mediated by their ability to displace the copper-coordinated water, these data do not rule out the possibility that a hydrolytic mechanism contributes to the nuclease activity. Indeed, UV−vis spectroscopic analysis of the mixture of Cu(II)-cyclen with NaN 3 , KI, or NaCl (Supplementary Figures S4−6) reveal that NaN 3 and KI displace the Cu(II) associated water while the NaCl does not (i.e., at the ratio used in the scavenging assay).…”
mentioning
confidence: 93%
“…In cell studies various nucleolytic copper complexes have shown high activity against cancer cells. [9][10][11] There are several approaches to increase the cleavage activity of cyclen metal complexes towards nucleic acids: multinuclear complexes, [12][13][14] attachment of nucleobase-affine moieties 15 or positively charged groups for better interaction with the phosphate backbone. 16 Whereas the 4N donor ligand cyclen has been frequently applied in such studies, heteroatom-substituted analogs are less common.…”
Section: Introductionmentioning
confidence: 99%
“…There are several approaches to increase the cleavage activity of cyclen metal complexes towards nucleic acids: multinuclear complexes, 12–14 attachment of nucleobase-affine moieties 15 or positively charged groups for better interaction with the phosphate backbone. 16…”
Section: Introductionmentioning
confidence: 99%